DIGITAL MARKETING FACTORS AND BUYING BEHAVIOUR IN THE FASHION INDUSTRY: EVIDENCE FROM GEN Z CONSUMERS IN AFRICA - Abdulraheem, Mulikat; Imouokhome , Ebun Omoniyi; Abdulsalam, Tajudeen Alaburo (Ekonomski pogledi, 2025)
The fashion industry, especially within e-commerce, stands as a highly dynamic sector, being the largest business-to-consumer (B2C) market with a global valuation of 768.7 billion in 2023 and an anticipated annual growth rate of 9.4%, potentially reaching 1,103.1 billion by 2027, underscoring its constant evolution. This growth is further propelled by the COVID-19 pandemic, which has brought significant health and economic challenges, greatly affecting the apparel, fashion, and luxury (AF&L) sectors. The research examines the effect of specific digital marketing factors on Gen Z buying behaviour across Africa’s fashion industry, concentrating on Congo (38%), Tanzania (32%), Nigeria (30%), and Egypt (27%), according to Gen Z’s population growth rate in Africa. A quantitative approach with a descriptive-correlational method was used, surveying 328 responses (85% sample rate) from Gen Z fashion consumers. Statistical analyses such as ANOVA, regression, and correlation coefficient were conducted, revealing significant evidence of the influence of digital marketing factors on Gen Z’s buying behaviour, with a strong correlation (R value of.862) and considerable explanatory power (R square value of.743). The study suggests that firms should develop engaging content, enhance awareness, and promote interaction, while regulatory bodies should monitor digital marketing practices. The empirical findings add to the expanding knowledge base within the African context, providing a foundation for future research to investigate specific cultural and socio-economic factors influencing Gen Z’s buying behaviours in other industries.